KEMISKINAN PEREMPUAN DALAM BINGKAI PEMBANGUNAN - Triana Sofiani; Endang Hernanik (Muwazah, 2011)
Abstract: Women are not getting a balanced distribution of development cake with men. This happens because the orientation of development still relies on macro economic growth, precisely to make women more marginalized in the frame construction. Further implication is the face of poverty attach to female faces. With the approach to women's empowerment are expected to have the capacity or ability to improve the independence and strength of him. So that women no longer serve as objects of development but as actors of development activities toward independence.